2019
DOI: 10.5720/kjcn.2019.24.5.395
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Its Association with the Dietary Behavior and Lifestyle of University Students in Cheongju

Abstract: Objectives: This study examined the association of the sleep quality and patterns with the dietary behavior, including snack and beverage consumption, taste preferences, as well as lifestyle of university students. Methods: The subjects were 406 university students in Cheongju, Korea, and the data were collected using a self-administered questionnaire. They were divided into two groups according to the Pittsburgh Sleep Quality Index (PSQI): good-quality sleepers (PSQI score ≤ 5) and poor-quality sleepers (PSQI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Excessive use of electronic devices can disrupt human biological rhythms due to the artificial lighting of the electronic devices that adversely affects sleep quality. Jin and Pae reported that 40.5% of individuals in their sleeping group used their smartphones for 2 to 4 hours and 48.8% for the non-sleep group, higher than in the sleeping group by 33.3% [20]. The results of this survey showed that college students' time using electronic devices increased by 34% compared to before COVID-19.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 72%
“…Excessive use of electronic devices can disrupt human biological rhythms due to the artificial lighting of the electronic devices that adversely affects sleep quality. Jin and Pae reported that 40.5% of individuals in their sleeping group used their smartphones for 2 to 4 hours and 48.8% for the non-sleep group, higher than in the sleeping group by 33.3% [20]. The results of this survey showed that college students' time using electronic devices increased by 34% compared to before COVID-19.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 72%
“…The investigations of a study in Cheongju illustrate that 52% of bad sleep standards were related to excessive smartphone usage [13]. In Saudi Arabia, university students are at danger of smartphone addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep deprivation has been associated with lifestyle factors in youths, particularly university students 8,9 . While regular aerobic exercise can improve sleep quality 10 , the mechanisms by which physical exercise affects sleep remain controversial.…”
Section: Introductionmentioning
confidence: 99%